WATER QUALITY OF SEAWEED CULTIVATION (Eucheuma cottonii) LOCATION IN OLD TAKALAR, MAPPAKASUNGGU DISTRICT, TAKALAR REGENCY - M, St. Madina; Syafiuddin, Syafiuddin; Samawi, Muh. Farid; Muhiddin, Amir Hamzah; Hatta, Muh. (Hasanuddin University, 2022)
This study was aimed to determine the water quality and seaweed growth and the relationship between oceanographic parameters and the growth of seaweed Eucheuma cottonii. This research was carried out from June-July 2021 at a seaweed cultivation location in Old Takalar, Mappakasunggu District, Takalar Regency. The seaweed cultivation method used is the longline method placed at three cultivation sites. Oceanographic parameters of physicochemical waters measured were temperature, salinity, pH, brightness, depth, current velocity, tides, nitrate, phosphate and dissolved oxygen. For the measurement of the growth of E. cottonii seaweed, the absolute growth was measured using One Way Anova analysis to determine differences in seaweed growth at each station of E. cottonii cultivation location. The correlation between oceanographic parameters and the growth of E. cottonii seaweed was analyzed using a correlation test. The results showed that the water quality at the cultivation site was within a reasonable range for seaweed cultivation in Old Takalar. The results of One Way Anova showed that there were significant differences in seaweed growth at each station where E. cottonii was cultivated. The results of the correlation test showed that the oceanographic parameters of the waters were very strongly correlated with the growth of E. cottonii seaweed, namely temperature, brightness, and depth.